1998
DOI: 10.1029/98je00394
|View full text |Cite
|
Sign up to set email alerts
|

Location and shape of the Jovian magnetopause and bow shock

Abstract: Abstract. Following Galileo's arrival at Jupiter in fall 1995, a total of six spacecraft have now sampled the Jovian magnetosphere. Using these data sets to investigate the average location and shape of the Jovian boundaries, we fit ellipse profiles to the observations, allowing for the disk-like shape of the magnetosphere and taking account of variable solar wind pressure. We find that the subsolar magnetopause location varies with solar wind dynamic pressure to power between -1/5 and -1/4, in contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 24 publications
8
109
3
Order By: Relevance
“…This contrasts with the study by Huddleston et al [1998] who found the Jovian magnetosphere to be more streamlined at high D P .…”
Section: Magnetopause Pressure Dependancecontrasting
confidence: 55%
See 3 more Smart Citations
“…This contrasts with the study by Huddleston et al [1998] who found the Jovian magnetosphere to be more streamlined at high D P .…”
Section: Magnetopause Pressure Dependancecontrasting
confidence: 55%
“…This allowed us to normalize the crossings to a fixed pressure so that we could fit models to the data to determine if the magnetosphere of Saturn exhibits polar flattening as has been observed at Jupiter by Huddleston et al [1998]. Even so, a considerable amount of scatter is present in the data, and further measures were taken to reduce this by comparing two different pressure estimates for each crossing and removing those where these estimates deviate by more than a factor of 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we therefore take L o to be half the subsolar radius of Jupiter's magnetosphere R mp , a value which is dependent on the dynamic pressure of the solar wind. Huddleston et al (1998) give an empirical formula for this dependence, that is…”
Section: Calculation Of the Reconnection Voltagementioning
confidence: 99%